Estimation of mass and radii for charged compact objects using a modified Chaplygin equation of state in the Buchdahl-I metric - A. Zahra; S. A. Mardan; Sana Saleem; Muhammad Bilal Riaz; Tomas Kozubek (PLoS ONE, 2025)
In this article, a class of static configurations for stellar equilibrium in relativistic charged spheres with anisotropic fluid is studied. The Buchdahl ansatz is employed to solve the Einstein-Maxwell field equations, which govern the behavior of charged, relativistic stellar objects. The matter distribution within the charged sphere is shown to satisfy all the necessary energy conditions, including the hydrostatic equilibrium condition. Several compact objects, such as GW 190814, PSR J0952-0607, PSR J0030+0451, PSR J0740+6620, GW 170817, PSR J1614-2230, PSR J2215+5135, and 4U 1608-52, are discussed to predict their masses and radii. These predictions are crucial for understanding the properties of compact stars, including neutron stars and possibly exotic stars. The physical properties of the charged sphere are examined, including mass, surface redshift, adiabatic index, and the speed of sound. The solutions are presented graphically, illustrating the structure of the stars. The results demonstrate that the maximum density and pressure occur at the center of the star, and these quantities are continuous and well-behaved throughout the star’s interior, avoiding singularities. These features offer strong support for the physical viability of the model, suggesting that the Buchdahl ansatz provides a realistic description of compact stars with electric charge and anisotropy.